Silêncio e comunicação: a literatura de Bartolomeu Campos de Queirós - Duarte, Lélia Parreira (Verbum – Analecta Neolatina, 2012)
This paper analyses several works by Bartolomeu Campos de Queirós, trying to show that his literature is built by two kinds of silence: the silenced one, that hides what could be said, and the silent one, the unnamable, a kind of irreducible sense only reached by an allusive way. Bartolomeu thus values his reader, also incomplete and desirous, authorizes them to be free and to play with language. He thus makes a communication without words possible, he talks of the frailty of the human being and of his anguish when facing life and death.